Ways to improve modern digitalization in accelerating economic reforms in Uzbekistan - Nasrulloev Hikmatullo Xabibulloevich (Genius Journals, 2025)
This article presents an analysis of the features of entering the information society abroad and in our country in the conditions of the digital economy, organizational and functional relations of participants in the information and communication market.
Keywords: tax; budget policy; budget